Pengembangan Aplikasi Mobile Learning Sebagai Media Pembelajaran Menggunakan Android Studio - Erdisna, Erdisna; Ningsih, Sri Restu; Suryana, Febriyanno; Hidayat, Rahmad; Putra, Deri Marse (Universitas Negeri Padang, 2024)
The rapid development of Science and Technology (IPTEK) has resulted in changes in the learning paradigm which are marked by changes in curriculum, media and technology. Technological innovation and information systems in the world of education, especially in universities, have their own attraction for students, because conventional learning sometimes makes students less creative in the learning process. In today's technological advances, Android cellphones have now become a necessity for society, especially among students and students. Smartphone media is very influential in the teaching and learning process between lecturers and students in the 21st century era and is one of the distance learning media solutions. The aim of this research is to develop a mobile learning application as a distance learning medium using Android Studio to simplify and increase the efficiency of the learning process in higher education. The method used in developing this system is the waterfall method with stages with the Unified Modeling Language (UML) system design tool. The result of this research is a mobile learning application using Android Studio which is effectively used as a distance learning medium in higher education. With this mobile learning application, Android-based learning has created interesting and dynamic learning for lecturers and students, so this creates many benefits and can minimize obstacles that have occurred in the learning process and help students like learning more.